Rapid free thiol rebound is a physiological response following cold‐induced vasoconstriction in healthy humans, primary Raynaud and systemic sclerosis. Issue 6 (27th March 2019) - Abdulle, Amaal Eman; van Roon, Anniek M.; Smit, Andries J.; Pasch, Andreas; van Meurs, Matijs; Bootsma, Hendrika; Bakker, Stephan J. L.; Said, Mohammad Y.; Fernandez, Bernadette O.; Feelisch, Martin; van Goor, Harry; Mulder, Douwe J.
Abstract: Raynaud's phenomenon (RP) is often the first sign of systemic sclerosis (SSc). Molecular mechanisms involved are incompletely understood, but reactive oxygen, nitrogen, and sulfur species are thought to play an important role in the pathogenesis of SSc. Free thiol groups play a protective role against oxidative stress and may represent an attractive therapeutic target. We aimed to investigate the effects of hypothermia‐induced vasoconstriction on the responsiveness of redox‐related markers. Thirty participants ( n = 10/group [SSc, primary Raynaud's phenomenon (PRP), healthy controls (HC)]) were included in this study. Fingertip photoelectric plethysmography was performed during a standardized cooling and recovery experiment. Venous blood was collected at four predetermined time points. Free thiols, NO‐derived species (nitros(yl)ated species, nitrite, nitrate), sulfate and endothelin‐1 were measured. Lower baseline concentrations of free thiols were observed in PRP and SSc patients (HC: 5.87 [5.41–5.99] μ mol/g; PRP: 5.17 [4.74–5.61]; SSc 5.28 [4.75–5.80], P = 0.04). Redox‐related markers remained unchanged during cooling. However, an unexpected increase in systemic free thiol concentrations was observed in all groups during the recovery phase. The response of this marker differed between groups, with a higher increase found in SSc patients (HC Δ = 1.30 [1.48–1.17]; PRP Δ = 1.04 [1.06–1.03]; SSc Δ = 1.72 [1.13–1.49], P = 0.04). NO‐derived species, sulfate and endothelin‐1 levels remained unchanged throughout the recovery phase. This exploratory study sheds light on the rapid responsiveness of systemic free thiol concentrations following reperfusion, which may reflect overall redox balance. The robust response to reperfusion in SSc patients suggests that reductive systems involved in this response are functionally intact in these patients. Abstract : In this exploratory study we show that circulating free thiols concentrations, which are an indirect measure of systemic oxidative stress, not only recover during reperfusion in all groups, but also reach levels that exceed baseline concentrations. This rapid antioxidant responsiveness may be the result of a physiological acute reaction to reperfusion, which may alter the oxidative balance.